Can antibiotics for enteritis or for urinary tract infection disrupt the urinary microbiota in rats? - Liu, Fengping; Hu, Lei; Sheng, Jiayi; Sun, Yifan; Xia, Qiang; Tang, Yifan; Jiang, Peng; Wei, Shichao; Hu, Jialin; Lin, Hao; Xu, Zhenyi; Guo, Wei; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background To establish antibiotic preregimes and administration routes for studies on urinary microbiota. Methods and materials Antibiotics for enteritis (Abx-enteritis) and UTIs (Abx-UTI) were administered via gavage and/or urinary catheterisation (UC) for 1 and/or 2 weeks. The effects of these Abx on the urinary microbiota of rats were examined via 16S rRNA sequencing and urine culture, including anaerobic and aerobic culture. Additionally, the safety of the Abx was examined. Results Abx-enteritis/Abx-UTI (0.5 g/L and 1 g/L) administered via gavage did not alter the microbial community and bacterial diversity in the urine of rats (FDR > 0.05); however, Abx-UTI (1 g/L) administered via UC for 1 and 2 weeks altered the urinary microbial community (FDR < 0.05). Rats administered Abx-UTI (1 g/L) via UC for 1 week demonstrated a distinct urinary microbiota in culture. Abx-enteritis/Abx-UTI administered via gavage disrupted the microbial community and reduced bacterial diversity in the faeces of rats (FDR < 0.05), and Abx-UTI administered via UC for 2 weeks (FDR < 0.05) altered the fecal microbiota. Abx-UTI (1 g/L) administered via UC did not alter safety considerations. In addition, we noticed that UC did not induce infections and injuries to the bladder and kidney tissues. Conclusions Administration of Abx-UTI via UC for 1 week can be considered a pre-treatment option while investigating the urinary microbiota.